The Impact Of Oil Price Fluctuations On The Internal Balance Indicators In Algeria: An Analytical Study Of The Period 2000-2023 - Bellarou Ali , Soltane Karima , Fertaki Djaber ,Ammari Samir (Elementary Education Online, 2025)
The prices of hydrocarbons in the world markets have known continuous fluctuations during the period 2000-2023 for reasons related to supply and demand factors in addition to other factors, which led to a direct impact on the indicators of internal balance in Algeria. The fuel sector represents about 28.8% on average of the gross domestic product during the period 2000-2023, which makes it one of the most important determinants of economic growth in Algeria, and oil tax revenues represent about 60% of the total public revenues of the state, which makes the performance of the state budget vulnerable to constant fluctuations in fuel prices, and the study period witnessed a significant decrease in inflation rates from about 28.5% to 11.8% in 2023, in addition to the increase in inflation rates from about 0.3% a year 2000 to about 9.3% in 2023.